Air dan Dampak Kelangkaannya bagi Perekonomian Masyarakat Urban: Studi Pustaka Pulau Jawa - Ratna Indah Lestari; Rina Ramadhani; Sherawali Sherawali; Ana Toni Roby Candra Yudha (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
The purpose of this study is to determine and analyze the effect of water resources on the economy of urban communities in Java and to answer the issue of clean water scarcity in 2040. The results of this study indicate that the issue of water scarcity in Java in 2040 is caused by climate change. population growth, land-use change, and water pollution. The suggestion in accordance with this is that all stakeholders are expected to be aware of and continue to monitor the availability of clean water by providing education and socialization at various professional and educational levels in order to obtain more sustainable use of water.